Attitude of Farmers towards Mixed Farming (Indian Journal of Extension Education, 2017)
The mixed farming through combination of crop production and their complementary livestock enterprises certainly create great potential of farms, establishing a complementary relationship between crop and livestock enterprises. To develop agriculture as a whole, economic condition of farmers is one of the important issues to analyze in popularizing use of mixed farming for agricultural development; there is a need to understand existing perception of the farmers towards relevance of mixed farming. As attitude assist individuals in processing complex information and to make decisions, an instrument has been developed to measure attitude of farmers towards mixed farming, for which “Scale Product Method” which combines the Thurston’s Equal Appearing Interval Scale (1928) for selection of the items and Likert’s Summated Rating Scale (1932) for ascertaining the response on the scale, was followed. The study was conducted on a random sample of 50 mixed farming adopters selected from ten villages of Anand taluka, of Anand district. It was observed that majority (90.00 %) of the farmers had positive attitude towards mixed farming. The positivism towards mixed farming was observed uniformly amongst the farmers with irrespective level of their age, education, farming experience, farm size, herd size, social participation, mass media exposure, extension contact, economic motivation and achievement orientation, while it was observed highly positive amongst the farmers with high level of scientific orientation.